PERAN DAN FUNGSI PENELITI DWI BAHASA (BILINGUAL): STUDI KASUS : WAWANCARA DENGAN INFORMAN DI DESA JATILUWIH, BALI INDONESIA - Bhaskara, Gde Indra (JURNAL MASTER PARIWISATA; Volume 05, Nomor 02, Januari 2019DO - 10.24843/JUMPA.2018.v05.i02.p11, 2019)
This study discusses the process of translating and adapting an interview content in Indonesian or regional (in this case Bali) into English in a Tourism study. This process certainly cannot be overlooked because of differences in Indonesian language and culture that are quite significant towards English and western culture. Therefore, this research offers a new insight in how a bilingual researcher takes action hence a translated interview will not lose its essence when it is analysed. The researcher used Computer Assisted/Aided Qualitative Data Analysis Software (CAQDAS) namely Nvivo in analyzing interviews from informants.  In this study it also explains about how the meaning of the contents of an interview lose the meaning at the analysis phase when error occurs. Keywords : bilingual, indonesian, bali, english, interview, research, researcher